Developmental assessment of children with special needs using a modified schedule of growing skills - Haironi, Y.; Mariah, A. (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Background There are currently no specific guidelines for developmental surveillance of children with special needs undergoing intervention programmes. Studies have looked at shortfalls of current methods and have recommended the need for a more psychometrically sound and standardized method of assessment.